Nestedness and systemic risk in financial networks - Michel Alexandre; Felipe Jordão Xavier; Thiago Christiano Silva; Francisco A. Rodrigues (Latin American Journal of Central Banking)
In this paper, we explore the relationship between node nestedness contribution and network stability in financial networks. We rely on data from the Brazilian interbank market. For each bank in the network, we computed the individual nestedness contribution (INC), along with two measures of systemic risk: systemic impact (SI) and systemic vulnerability (SV). The INC is computed considering the different roles played by the banks: lender and borrower. We found that borrowing banks with a higher INC would cause more damage to the network if they were hit by a shock — i.e, they have a higher SI. Moreover, lending banks with a higher INC are more vulnerable to shocks on the network.